ORGANIZATIONAL SILENCE, ORGANIZATIONAL TRUST, AND ORGANIZATIONAL COMMITMENT: Business - Ahmadian, Sahar; Astrabeh, Saeed; Ejrami, Mohsen (Transpublika Publisher, 2023)
Organizational silence limits the effectiveness of organizational decisions and change processes. This is a problem that is currently plaguing organizations, and it causes most organizations to suffer from very little employee comments and opinions that can reduce the effect of organizational trust on organizational commitment. Therefore, the present research investigates the mediating role of organizational silence and its dimensions including; Deviant silence, Disengaged silence, Diffident silence, Defensive silence, Relational silence, and Ineffectual silence in the effect of organizational trust on organizational commitment. The method of collecting information was a standard questionnaire. The statistical population of the research includes 75 experts of Automotive Company in Iran. The questionnaire was distributed among 75 people and finally 70 questionnaires were returned healthy and analyzable. For the statistical analysis in the inferential statistics section of the research, all the analyses were done using the structural equation technique and the partial least squares method with the help of SMART PLS software. The results of data processing showed that relational silence, diffident silence, and deviant silence play a mediating role in the effect of organizational trust on organizational commitment. Other research results did not confirm the mediating role of defensive silence, ineffectual silence, and disengaged silence in the effect of organizational trust on organizational commitment. The results of the research can be used for automotive company's managers to identify the types of silences that exist in the organization and increase the organizational trust and commitment of company employees